O dwóch pułapkach kreacjonizmu - Ługowski, Włodzimierz (Filozofia Nauki, 2001)
The author attempts to answer the question, how it is possible that many scholars - including those representing prestigious universities and research institutes - are ready to consider creationists critique of the origin- of-life theories as "valuable", "scientifically useful", "cogent", and "clarifying our thinking". The answer seems to be simple: the same metascientific assumptions, which constitute a basis of antievolutionistic argumentation, still live in the philosophical consciousness (or subconsciousness) of a lot of scientists. Among these assumptions is he thesis that order does not arise from disorder and the principle of the uniformity of nature.